Emergency Vehicles: Police Cars - Ethan, Eric. (Milwaukee, WI : Gareth Stevens Pub., 2002)
An introduction to police cars and the way in which police officers use them in their work.
Includes bibliographical references (p. 23) and index.
Accelerated Reader AR
Keywords: Police vehicles -- Juvenile literature; Police patrol -- Juvenile literature